2014
DOI: 10.1186/1477-7819-12-311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and survival analysis of 36 cases of primary fallopian tube carcinoma

Abstract: BackgroundPrimary fallopian tube carcinoma (PFTC) is rarely seen clinically. Herein, we investigate the clinical and pathological characteristics and appropriate therapies for PFTC.MethodsA total of 36 patients for whom PFTC was pathologically confirmed from January 2001 to July 2011 in Beijing Hospital of Gynecology and Obstetrics, an affiliate of Capital Medical University, were retrospectively analyzed.ResultsA total of 36 cases underwent surgical staging in our hospital: 47.2% were early stage cases , and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…In our current series, the mean age was 57.35±9.01 years, and univariate analysis is failed to find a significant correlation between the age and survival results. Meanwhile, 42 (73.7%) are postmenopausal patients with a mean postmenopausal period of 8.18±8.12 years (1-33years) in our cohort study, which is similar to previous reports [10,11]. All the evidence suggest postmenopausal women may be more prone to this malignancy.…”
Section: Discussionsupporting
confidence: 90%
“…In our current series, the mean age was 57.35±9.01 years, and univariate analysis is failed to find a significant correlation between the age and survival results. Meanwhile, 42 (73.7%) are postmenopausal patients with a mean postmenopausal period of 8.18±8.12 years (1-33years) in our cohort study, which is similar to previous reports [10,11]. All the evidence suggest postmenopausal women may be more prone to this malignancy.…”
Section: Discussionsupporting
confidence: 90%
“…Most studies failed to identify correlation between prognosis and omentectomy or omentum metastasis, 11,21,22 but one study reported omentum metastasis as an independent risk factor of prognosis. 35 In our study, the multivariate analysis revealed no significant difference between these factors in relation to survival, indicating their undefined role for PFTC.…”
Section: Discussioncontrasting
confidence: 45%
“…CA125 is a useful marker for PFTC progression during the follow‐up remission period after treatment, where it has been reported that CA125 levels increase prior to a clinical diagnosis of recurrence . Moreover, a recent study showed that CA125 had 57.6% (19/33) sensitivity in diagnosing PFTC, and was correlated to prognosis . However, because of the limitation of low specificity, CA125 is not very effective in the diagnosis of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…42 Moreover, a recent study showed that CA125 had 57.6% (19/33) sensitivity in diagnosing PFTC, and was correlated to prognosis. 43 However, because of the limitation of low specificity, CA125 is not very effective in the diagnosis of malignancies. HE4 is a novel, promising marker for diagnosis in women with suspected PFTC and when combined with CA125 has been proven to enhance sensitivity and specificity for the diagnosis of ovarian cancer; PFTC is similar to ovarian cancer and there is a lack of optimal management.…”
Section: Discussionmentioning
confidence: 99%